2011
DOI: 10.1007/s12078-011-9087-3
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of CO2, Ethanol, Hop Acids and Sweetener on Flavour Perception in a Model Beer

Abstract: Beer is a complex beverage. Beer flavour is a multisensory experience in which, in addition to aroma volatiles, CO 2 , ethanol, bitterness (hop acids) and sweetness all contribute. To investigate the interactions between these fundamental components, a model beer system was developed using representative ingredients. Samples, selected according to a D-optimal design, were assessed by sensory profiling techniques by a trained panel. Predictive polynomial models generated from mean panel data described variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 60 publications
9
37
2
1
Order By: Relevance
“…However, this increase appears to be dependent on polyphenol concentration. An increase in astringency was observed for a low concentration of hop acid but a decrease in its perception was obtained at 600 mL/L of hop acid (Clark et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, this increase appears to be dependent on polyphenol concentration. An increase in astringency was observed for a low concentration of hop acid but a decrease in its perception was obtained at 600 mL/L of hop acid (Clark et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Some authors found a decrease in bitterness with CO 2 in beer but only over 300 mL/L of hop acid with an increased bitterness up to 150 mL/L (Clark et al, 2011). ComettoMuniz et al (1987) observed a similar effect on quinine sulfate solution with an increase in bitterness for low concentrations and a decrease for high concentrations.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Říz piva je způ-soben rozpuštěným oxidem uhličitým. Je vnímán mechanoreceptory (hmatovými receptory), které jsou aktivovány přítomností bublinek v kapalině a také receptory bolesti, které reagují na konverzi oxidu uhličitého na kyselinu uhličitou, může být ovlivněn hodnotou pH a koloidními látkami v pivu (Clark et al, 2011).…”
Section: Brewing Trialsunclassified
“…It is perceived by mechanoreceptors (tactile receptors) which are activated by the presence of bubbles in the liquid, and also by pain receptors that react to the conversion of carbon dioxide to carbonic acid. It can be infl uenced by pH and colloidal substances in beer (Clark et al, 2011).…”
Section: Brewing Trialsmentioning
confidence: 99%